Effect of IASTM on Low Back Pain Patients: Study Protocol - Noel Samuel Macwan; Vandit Gandhi (Innovations in Biological Science Vol. 9, 2024)
Background: Since low back pain (LBP) is associated with both disability and absenteeism, it is an important public health concern that often results in referrals to medical services. LBP is positioned below the costal edge and above the gluteal curvature. Since up to two-thirds of adults experience LBP at some point in their life, it is the most common musculoskeletal ailment. The literature has documented a variety of treatment modalities for LBP, ranging from electro-physical agents to patient education, contingent on the severity of the symptoms. Even with treatment for LBP, recurrence is prevalent, necessitating the use of an increasingly effective method such as IASTM. In addition to conventional treatment for low back pain, it has been a popular therapeutic strategy for myofascial constriction in recent years. Very few publications have examined the impact of IASTM on low back pain, according to a literature search. Thus, the goal of this research is to determine how well IASTM works for those with low back discomfort. Methodology: All participants coming to Physiotherapy OPD were screened as per the routine musculoskeletal assessment. Those who met the inclusion criteria and were willing to participate in the study were requested to fill out the informed consent form. Those participants who fell under the exclusion criteria were excluded from the study. Participants were randomly allocated to either the Interventional group or the control group with the use of simple randomization. Once the assessment was completed the patients were treated as per the treatment protocol devised for the Interventional group or control group respectively. Patients in both groups (Interventional group and control group) received 2 days of treatment (on 1st day and 7th day) in a week. Outcome Measures: Primary outcome–Modified Schober’s test, Secondary outcome: Visual Analog scale, Oswestry disability index. Statistical Analysis: Both descriptive and inferential statistics were done with taking help of a Biostatistician. The latest version of SPSS software available with the Biostatistician was used for doing the statistical analysis. Conclusion: This study protocol presents an RCT on the efficacy of IASTM and General Back exercises in patients with Low back pain. The results of this RCT will be helpful in contributing better insights into the efficacy of IASTM on pain levels, range of motion of the lumbar spine and activities of daily living performance in LBP subjects. Clinical Trial Registration: The study is registered with the Clinical Trials Registry-India (CTRI), with the registration number for the trial being CTRI/2023/05/052764.